IMPLEMENTATION OF ACCOUNTING INFORMATION SYSTEM AT BUMDES IN IMPROVING THE QUALITY OF VILLAGE FINANCIAL REPORTS - Pandu Adi Cakranegara; Irwan Moridu; Shevti Arbekti Arman; Sugianto Sugianto; Ernawaty Usman (Jurnal Ekonomi, 2022)
The Accounting Information System manages the sales and accounts receivable process, from recording to financial report production. This system will provide speedy, precise, and accurate information services, and BUMDes Adnyana Tunggal will find this information extremely useful in gauging the company's growth. Each component of BUMDes must operate optimally. In view of the relevance of stimulating the village economy and aiding the village communities, it is vital to link existing business processes in BUMDes with systems so that controlled business operations are quicker, more exact, and generate accurate reports. This study employs the collection of both primary and secondary data for its data collecting. This sales and accounts receivable data management information system includes the printing of orders, sales transaction receipts, accounts receivable cards, and documentation of accounts receivable transactions, among other features. In addition, this system provides sales reports, accounts receivable reports, and profit and loss reports, which can help BUMDes manage financial reports and enhance the financial transparency and quality of villages.